inggris - Muliati; Na'imah; Nur Sa'idah; Badrun; Arif Prasetyo (Tadbir: Jurnal Manajemen Pendidikan Islam, 2025)
This study was conducted to find concrete innovations in the leadership of the madrasah principal in improving the quality of education at MTs N 9 Bantul. The quality of education is the main part that is applied in Islamic educational institutions in order to achieve good quality education. The madrasah principal is the main driver in the madrasah in achieving the goal of quality education. This study uses a descriptive qualitative research type. Data collected through in-depth interviews, observations, and documentation with the Madrasah Principal and the Deputy Madrasah Principal for student affairs. The results of this study indicate that the innovation of the madrasah principal's leadership in improving the quality of education in the 5.0 era can be found in the implementation of nine (9) superior programs, namely (1) Madrasah Achievement Activities (GSM) (2) Masamba Literacy Movement (GLM) (3) Sadam (Sadar Adiwijaya Masamba), (4) ODOT (One Day One Thousand), (5) PUTIH (Publication Tiada Henti) (6) Saturday Masemba Dhikr (SMB) (7) JUMARIA (Cheerful Friday) (8) FORSIMBA ( Synergy Forum) Committee , Community, and Masemba ) (9) Parent, Teacher and Student Study Group (PGS) . Furthermore, the second finding is the existence of partnerships and collaborations that will facilitate cooperation both within the internal and external scope of the organization to support the ongoing running of the madrasah program. Then, the third finding is the empowerment of educators and education personnel so that students will find it easier to understand the material given by students.